Multirate Linear Quadratic Gaussian controllers for linear time-invariant systems - Chua, Say Yong. (2009)
In the last decade and particularly the last several years, multirate digital control has been an area of active and prominent research. Numerous interesting results have been reported in the literature [1]-[21]. Multirate digital controllers are a special class of periodic digital controllers which employ periodically time-varying mechanisms. In these schemes, input updating and output sampling are performed with different rates or at different time instants. It has been proved that such controllers can satisfactorily respond to a variety of design requirements such as pole assignment, strong stabilization, model matching, et al.